Transnational Corporations and Global Environmental Governance - Jennifer Clapp (Handbook of Global Environmental Politics, 2005)
The first Handbook of original articles by leading scholars of global environmental politics, this landmark volume maps the latest theoretical and empirical research in this young and growing field. Captured here are the dynamic and energetic debates over concerns for the health of the planet and how they might best be addressed. The introductory chapters explore the intellectual trends and evolving parameters in the field of global environmental politics. They make a case for an expansive definition of the field, one that embraces an interdisciplinary literature on the connections between global politics and environmental change. The remaining chapters are divided into three broad themes – states, governance and security; capitalism, trade and corporations; and knowledge, civil societies and ethics – with each section providing a cohesive discussion of current issues. In-depth explorations are given to topics such as: global commons, renewable energy, the effectiveness of environmental cooperation, regulations and corporate standards, trade liberalization and global environmental governance, and science and environmental citizenship. A comprehensive survey of the latest research, the Handbook is a necessary reference for scholars, students and policymakers in the field of global environmental politics.